Processing and interpretation of reflection seismic data from Isfjorden, Svalbard - Haugland, Ingrid (The University of Bergen, 2023)
The geology of the present-day Svalbard is complex and has formed through several million years of repeated episodes of orogeneses, uplift, deformation and erosion. This has resulted in complex deformation structures and fault zones, as well as an abnormal high seabed velocity (greater than 4.5 km/s). These factors represent a challenge for both processing and interpretation. This study attempts to process and interpret four 2D multichannel seismic lines that were acquired in inner Isfjorden, Sassenfjorden and Nordfjorden during the 2002 SVALEX student course. The lines include the major N-S trending Billefjorden Fault Zone (BFZ) in Sassenfjorden and the Blomesletta Fault in Nordfjorden. The seismic data was initially contaminated by strong and short-interval multiples that almost completely hid the primary reflections. The main focus during processing was to attenuate these in the best possible way to obtain a multiple-free seismic image without significantly reducing the overall data quality. This was approached by the application of various processing sequences, in which deconvolution and f-k filtering were essential and applied several times. Stacking and muting also had positive effects in reducing the remaining multiple energy. Stratigraphic units from the seabed till basement have been interpreted, which include the base Jurassic, Triassic, Permian, Carboniferous and Devonian sedimentary successions, and the crystalline basement “Hecla Hoek”. The fault geometry of the BFZ has been interpreted as a major reverse western fault and normal eastern fault, both dipping steeply to the east. The BFZ has likely been reactivated several times, but its formation is linked to the Caledonian Orogeny that lasted from Early Ordovician to Early Devonian. The reverse fault displaces the basement rock against the Devonian basin, while the normal fault coexists with the presence of a distinct syn-rift half-graben structure, formed during the Caledonian collapse. The Blomesletta Fault is interpreted as a reverse fault, ...